2021
DOI: 10.1002/gj.4169
|View full text |Cite
|
Sign up to set email alerts
|

Mineralogical and geochemical constraints on the provenance and depositional setting of Sri Lankan marbles

Abstract: Proterozoic high‐grade marbles cover a significant portion of the Highland Complex (HC) of Sri Lanka. Although many studies on metamorphic silicate rocks of the country have been carried out, marbles, which can be used as a tool to interpret the evolution history of the crust, has been paid little attention. The present study aims to understand the genesis and characteristics of protolith of these marbles by investigating their mineralogy and geochemistry. The studied marbles occur as bands intercalated with p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 103 publications
1
0
0
Order By: Relevance
“…Concentrations of SrO (0.01–0.09 wt. %) of calcite and dolomite in the studied marbles are comparable to those of sedimentary origin marble (e.g., Borra, India: 91 , 92 ; Sol Hamed, ED-Egypt: 5 ; Engabreen, Norway: 93 ; Sri Lanka: 94 ). suggested that the source of SiO 2 and Al 2 O 3 in ER and DG-marbles is most likely country serpentinite rocks, as evidenced by the strong correlation between Cr contents and these oxides.…”
Section: Resultssupporting
confidence: 64%
“…Concentrations of SrO (0.01–0.09 wt. %) of calcite and dolomite in the studied marbles are comparable to those of sedimentary origin marble (e.g., Borra, India: 91 , 92 ; Sol Hamed, ED-Egypt: 5 ; Engabreen, Norway: 93 ; Sri Lanka: 94 ). suggested that the source of SiO 2 and Al 2 O 3 in ER and DG-marbles is most likely country serpentinite rocks, as evidenced by the strong correlation between Cr contents and these oxides.…”
Section: Resultssupporting
confidence: 64%